Coping and Resilience during the Food, Fuel, and Financial Crises - Heltberg, Rasmus; Hossain, Naomi; Reva, Anna; Turk, Carolyn (Taylor and Francis, 2013)
This article aggregates qualitative field research from sites in 17 developing countries to describe crisis impacts and analyse how people coped with the food, fuel, and financial crises during 2008–2011. The research uncovered significant hardships behind the apparent resilience, with widespread reports of food insecurity, debt, asset loss, stress, and worsening crime and community cohesion. There were important gender and age differences in the distribution of impacts and coping responses, with women often acting as shock absorbers. The more common sources of assistance were family, friends, community-based and religious organisations with formal social protection and finance less important. The traditional informal safety nets of the poor became depleted as the crisis deepened, pointing to the need for better formal systems for coping with future shocks.